Tannic acid assisted metal–chelate interphase toward highly stable Zn metal anodes in rechargeable aqueous zinc-ion batteries - Hu, Nan; Qin, Hongyu; Chen, Xiangyou; Huang, Yanping; Xu, Jing; He, Huibing (Frontiers in Chemistry, 2022)
Aqueous zinc-ion batteries (AZIBs) have attracted extensive attention due to their eco-friendliness, intrinsic safety and high theoretical capacity. Nevertheless, the long-standing Zn anode issues such as dendrite growth, hydrogen evolution and passivation greatly restrict the further development of AZIBs. Herein, a metal-chelate interphase with high Zn affinity is constructed on the Zn metal surface (TA@Zn) via dipping metallic Zn into TA solution to address the aforementioned problems. Benefiting from the abundant hydrophilic and zincophilic phenolic hydroxyl groups of TA molecules, the metal-chelate interphase shows strong attraction for Zn2+ ions, guiding uniform zinc deposition as well decreasing Zn2+ migration barrier. Consequently, the TA@Zn anode displays an extended lifespan of 850 h at 1 mA cm-2, 1 mAh cm-2 in the Zn|Zn symmetrical cell and a high Coulombic efficiency (CE) of 96.8 % in the Zn|Ti asymmetric cell. Furthermore, the Zn|V2O5 full cell using TA@Zn anode delivers an extremely high capacity retention of 95.9 % after 750 cycles at 2 A g-1. This simple and effective strategy broadens the interfacial modification scope on Zn metal anodes for advanced rechargeable Zn metal batteries.